Eco-Spiritualism on Social Empowerment: Indigenous Approach toward Environment Sustainability - Taufiq, Imam; Choirun Nisa, Lulu; Khoiruddin Zuhri, Mishbah; Megah Safitri, Ririh; Sessiani, Lucky Ade; Makmun, Muhammad (Universitas Diponegoro, 2021)
The world is changing, the environmental crisis is happening, the life of any living being is on the line. Nature is facing challenges and degradations that will extended to effect on human welfare and all other life on earth. As in the 2030 Sustainable Development Goals agenda, world leaders command every organization to play a role in protecting the planet from degradation, undertake urgent actions to perform sustainable resource management. UIN Walisongo Semarang is answering the call and respond to this global issues by declaring a vision statement to be a “Green Campus”. It is not merely a statement, but a commitment to take responsibility in protecting and conserving the nature, applied in all activities under the Three Pillars of Higher Education (Education, Research, and Community Services). This paper aimed to elaborate the distinct concept and approach of community service activities implemented in UIN Walisongo Semarang. Eco-Spiritualism Social Empowerment program designed based on fundamental spiritual and religious values about how human connect with nature, and so this connection create a reciprocal-inseparable relationship. How human affects nature, and otherwise, will create a belief and values directing human’s behavior toward nature. Therefore, a spiritual approach considered to be an effective way to empower people in order to create an eco-friendly society. Eco-Spiritualism Social Empowerment program implemented in both rural and urban area, are showing great results on recycle and waste management, plastic waste utilization and creating value added products, skill development and sustainable social empowerment